KNOWING THE WORLD THROUGH LANGUAGE ‒ PHRASEOLOGISMS IN THE NOVEL ZABLUDA SVETOG SEBASTIJANA BY VLADIMIR TABAŠEVIĆ - Mijana Č. Kuburić Macura; Sandrijela B. Kasagić (Filolog, 2025)
This article first outlines the dominant features of the author's narrative manner, i.e. syntactic and lexical features of the novel. In the central part of the paper, an analysis of the unusual use of phraseology is presented, which illustrates the acquisition of the mother tongue in the 1990s war circumstances. Phraseologisms are analysed primarily based on their function in the text, but they are also commented on from the point of view of their dictionary description, formal structure and semantics. Analysing the text revealed several striking strategies that produce a vivid and authentic picture of language development. In the first place, it is a meta-linguistic and meta-contextual separation of the narrator and an observation of the linguistic situation in which the newly adopted phraseological units are perceived and produced; then playing with the inadequate use of phraseology, which indicates insufficient phraseological competence; and understanding and interpreting phraseology in its literal meaning, which is also a characteristic of language acquisition.